1987
DOI: 10.1002/chin.198707035
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Detection and Structural Study of a New Family of Layered Compounds of the General Composition (UO)2RS3 (R: Gd to Lu and Y).

Abstract: The novel title compounds are obtained in the course of reaction tests between UOS and various sulfides, which are positive only in the case of the sulfides R2S3 (R: Gd to Lu, Y) at temp. as high as 1500‐1900 °C. The crystal structure of the isotypic compounds is solved in the case of (UO)2ErS3, which crystallizes in the tetragonal system (I4/mmm, Z=2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…One such group of quaternary chalcogenides belongs to the hexagonal crystal system space group P6 3 , first reported in 1968 as the cell parameters calculated from powder X-ray diffraction data, and has proven to be a remarkably robust structure type. 8 Single-crystal structure investigations revealed that these compounds belong to the Ce 6 Al 3.33 S 14 9 or La 3 CuSiS 7 structure type. 10 Today, a large number of compounds are known with this structure type with the general formula A 6 B 2 C 2 Q 14 or A 3 BCQ 7 , while some have vacancies within the [A−B] metal network.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One such group of quaternary chalcogenides belongs to the hexagonal crystal system space group P6 3 , first reported in 1968 as the cell parameters calculated from powder X-ray diffraction data, and has proven to be a remarkably robust structure type. 8 Single-crystal structure investigations revealed that these compounds belong to the Ce 6 Al 3.33 S 14 9 or La 3 CuSiS 7 structure type. 10 Today, a large number of compounds are known with this structure type with the general formula A 6 B 2 C 2 Q 14 or A 3 BCQ 7 , while some have vacancies within the [A−B] metal network.…”
Section: ■ Introductionmentioning
confidence: 99%